PENGARUH SOFT SKILL, PERILAKU INOVATIF DAN PENGGUNAAN TEKNOLOGI TERHADAP KINERJA PEGAWAI PADA ARJ88 STORE X ELORA GIRLWEAR - Ayuni, Ni Made Sri; Diah Amanda Sanjiwani, I Gst Agung Ayu (Komunitas Manajemen Kompetitif, 2024)
This research aims to determine the influence of soft skills, innovative behavior and use of technology on employee performance at Arj88 Store X Elora Girlwear. The data analysis techniques used in this research are multiple linear regression analysis, classical assumption testing, model feasibility testing (Goodness of Fit), and hypothesis testing, research results using the SPSS Version 21.0 for Windows application. The results of this study indicate that soft skills have a positive and significant effect on employee performance at Arj88 Store X Elora Girlwear, with a positive influence between soft skills on employee performance at work at Arj88 Store X Elora Girlwear. Innovative behavior has a positive and significant effect on employee performance at Arj88 Store X Elora Girlwear, with a positive influence between innovative behavior and employee performance at work at Arj88 Store X Elora Girlwear. The use of technology has a positive and significant effect on employee performance at Arj88 Store X Elora Girlwear, with a positive influence between the use of technology on employee performance at work at Arj88 Store X Elora Girlwear. Based on the results of the f-test, it is known that the value of f-count> f-table, namely 28.004> 3.16, this indicates that soft skills, innovative behavior and the use of technology jointly affect employee performance.